2023
DOI: 10.1021/acs.jctc.3c00232
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Covalent Drug Design Workflow Using Site Identification by Ligand Competitive Saturation

Abstract: Covalent drug design is an important component in drug discovery. Traditional drugs interact with their target in a reversible equilibrium, while irreversible covalent drugs increase the drug−target interaction duration by forming a covalent bond with targeted residues and thus may offer a more effective therapeutic approach. To facilitate the design of this class of ligands, computational methods can be used to help identify reactive nucleophilic residues, frequently cysteines, on a target protein for covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 78 publications
(181 reference statements)
0
9
0
Order By: Relevance
“…This approach allows for assessment of GFE scores of individual classified atoms within the ligand that may be summed yielding the LGFE score that represents the ligand binding affinity. 3,5,50,57 been shown that ligand ranking using the SILCS methodology is comparable with the FEP approaches 51 while offering an improvement in computational speed of over 2 orders of magnitude. In addition, SILCS-MC has been used in conjunction with FragMaps for lipid bilayers to calculate the free energy profiles of ligands across the bilayers, information subsequently used in conjunction with a deep neural net to develop an artificial intelligence tool for prediction of ligand passive permeability.…”
Section: Introductionmentioning
confidence: 99%
“…This approach allows for assessment of GFE scores of individual classified atoms within the ligand that may be summed yielding the LGFE score that represents the ligand binding affinity. 3,5,50,57 been shown that ligand ranking using the SILCS methodology is comparable with the FEP approaches 51 while offering an improvement in computational speed of over 2 orders of magnitude. In addition, SILCS-MC has been used in conjunction with FragMaps for lipid bilayers to calculate the free energy profiles of ligands across the bilayers, information subsequently used in conjunction with a deep neural net to develop an artificial intelligence tool for prediction of ligand passive permeability.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study of several popular docking tools by Keserű et al observed a protein-dependent performance of docking approaches and thus recommends choosing an optimal docking tool based on the target protein. To avoid these uncertainties and to increase accuracy, it is often recommended to use a combination of tools and/or develop a robust workflow to achieve best results. To summarize, covalent docking is useful in ranking different inhibitors with the same warhead and/or to generate an initial binding pose that incorporates both the orientation of the covalent bond as well as the optimal non-covalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed workflow of the SILCS-covalent drug design process. Reproduced with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations